Seismic Behavior Of Full-Scale Piles In Improved Soft Clay - Bradley J. Fleming (Deep Foundations Institute)
Although soil improvement and its application to deep foundations is gaining popularity in the engineering community, this technique is not widely used in high seismic regions due to lack of fundamental understanding of both the behavior of improved soils under high-strain cyclic loading and the interactions between the pile, improved soil, and unimproved soil. This paper describes part of an ongoing Network for Earthquake Engineering Simulation (NEES) project, where two identical full-scale steel pipe piles were driven at a soft clay site in Oklahoma. The soil surrounding one of these piles was improved using the cement deep soil mixing technique in order to enhance its lateral load behavior. Both piles were tested for seismic resistance using dynamic and quasi-static loading. The pile in unimproved soil provided larger displacements with limited lateral force resistance. This pile was subjected to lateral displacements of up to 400 mm, but experienced minimum inelastic actions. On the other hand, the pile in improved soil reached its lateral capacity at a displacement of 100 mm, at which point the critical region at the base of the pile just above the improved ground experienced buckling and fractured due to low cycle fatigue. Compared to the pile in unimproved soil, the improved ground increased the system strength by 42%. Although the soil was improved over 2900 mm, the effective improvement depth was approximately 1300 mm below the ground surface. In this paper, it is demonstrated that the effects of block type soil improvement of limited horizontal and vertical dimensions can be described using a simplified theoretical approach involving a modification to the well-known p-y representation of soil response. An example using this method is presented and shown to give adequate support to a standard 12-inch diameter steel pipe pile embedded in soft soil.